Cobble Hill [compact disc, unabridged] - Von Ziegesar, Cecily (Simon & Schuster Audio, 2020)
Welcome to Cobble Hill. In this eclectic Brooklyn neighborhood, private storms brew amongst four married couples and their children. There's ex-groupie Mandy, so underwhelmed by motherhood and her current physical state that she fakes a debilitating disease to get the attention of her skateboarding, ex-boyband member husband Stuart. There's the unconventional new school nurse, Peaches, on whom Stuart has an unrequited crush, and her disappointing husband Greg, who wears noise-canceling headphones everywhere. A few blocks away, Roy, a well-known, newly transplanted British novelist, has lost the thread of his next novel and his marriage to capable, indefatigable Wendy. Around the corner, Tupper, the nervous, introverted industrial designer with a warehouse full of prosthetic limbs struggles to pin down his elusive artist wife Elizabeth. She remains, elusive.